Weaponomics : The Global Market for Assault Rifles - Killicoat, Phillip (World Bank, Washington, DC, 2012)
This paper introduces the first effort to quantitatively document the small arms market by collating field reports and journalist accounts to produce a cross-country time-series price index of Kalashnikov assault rifles. A model of the small arms market is developed and empirically estimated to identify the key determinants of assault rifle prices. Variables which proxy the effective height of trade barriers for illicit trade are consistently significant in determining weapon price variation. When controlling for other factors, the collapse of the Soviet Union does not have as large an impact on weapon prices as is generally believed.